Enhanced Image Encryption Scheme for Securing Iris Template using a Novel Hybrid Fractional Fourier DRPE - Vasuki, R; Singh, K Ranjith (Journal of Electrical Systems, 2024)
Security becomes more and more necessary as a result of the significant advancements in computers and communications as well as the widespread use of electronic media, particularly in organizations where information is increasingly vital. Earlier methods, like traditional cryptography, employ encryption keys, which are lengthy bit strings that are extremely difficult to memorize. Additionally, it is easily attackable utilizing the brute force attack method. Since biometric traits are always changing and ever-living, biometrics-such as voice, fingerprints, and iris-provide a unique means of identifying an individual and a safe stream cipher in place of more conventional cryptographic approaches. Information security is becoming more and more necessary as information technology advances. The biometricbased encryption technology has advanced quickly to meet demands for increased convenience and security. Among them, iris technology has grown in importance as a subject of study for information security researchers because of the constancy of iris traits and their difficulty being copied. In this paper, the iris portion is extracted from the eye and a novel encryption technique which is a hybrid combination optical cryptography and Fast Fourier transformation is presented. The Idea behind the technique is to extract the iris by means of novel encryption technique. After encryption process, the decryption is performed. The common iris database MMU and IITD is used to conduct the simulation experiment. The results demonstrate that the technique may significantly increase the security of the encryption and decryption process as well as the consistency of iris encryption.